Development and Validation of UV-VIS Spectrophotometric Method for Estimation of Methylprednisolone from Dissolution Media - Mhetre M. N.; Kalshetti M. S. (International Journal of Scientific Research in Science and Technology, 2024)
A simple, accurate UV-Spectrophotometric method has been developed using a dissolution media, 0.1% Tween 20 as a solvent to determine the methylprednisolone. At a predetermined λmax of 245 nm, method was proved linear in the range of 5-40 μg/ml with good correlation coefficient (R2=0.998) and excellent recovery (between 98 and 101%). This method was successfully applied to the determination of methylprednisolone from dissolution media, 0.1% Tween 20 aqueous solution. This method can be employed for the dissolution study of methylprednisolone in injectable suspension.
Keywords: Methylprednisolone; UV-Spectrophotometer; Dissolution; Injectable Suspension